The Role of Social Worker in Developing Information Needs among Street Children (A case study in Surabaya Indonesia) - Mutia, Fitri (International Journal of Engineering and Technology, 2018)
Information needs among children is interesting topic because the way they looking for information are difference with adult. Usually children require assistance from certain person to help them finding the right and valid information. In the case of street children who living in social institutions, social worker role is very important to help then finding information because most of street children have no formal education, so they need to directed at finding and retrieving information to develop their knowledge. The number of street children in Surabaya increasing every year, this condition forced Surabaya Social Service to implement appropriate strategies to reduce the problems related to street children. Ones were through the assistance from the Regional Technical Implementation Unit (UPTD) "Kampung Anak Negeri" staff in Surabaya. The aim of this research is to describe the role of social worker in developing information needs of street children in UPTD Surabaya. Data in this research was collecting using questionnaire. The research method is quantitative descriptive with total population (32 people) become respondent, consisting of all street children (15 children) and social worker (17 person) in UPTD "Kampung Anak Negeri" Surabaya. The result show that social worker in UPTD Surabaya have a potential role in developing information needs among street children, especially when they playing as facilitator and educator roles. Social worker support street children to find information that as many 9 (60%) street children mostly need information related to their hobbies (such as music, sports). Around 13 (76.5%) social workers provide an opportunity for them to disclose that information, and for more aware and independent in the process of finding information 12 (70.6%) social worker teaches street children a strategy to obtain appropriate information like visit the library or using the internet (with permission). According to 12 (70.6%) social worker, the ability of street children to finding information is still dependent on social worker role as facilitator and educator. But, the social worker role as community representatives and technical, become a supporting role for the success of finding information that street children needs..Â